Analisis Keberlanjutan Usahatani Andaliman di Kabupaten Toba - Sitorus, Abdoni; Rauf, Abdul; Lindawati, Lindawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Andaliman as a typical biodiversity of North Sumatra that grows wild in the Toba and Tapanuli lake areas and is widely found in Toba Regency. Toba Regency is the largest producer of andaliman in North Sumatra with a planting area of 274 Ha and a production of 110.17 tons per year. Andaliman plants experience price fluctuations throughout the year ranging from Rp. 10,000 to Rp. 400,000. Andaliman plants are also quite difficult to cultivate so that Andaliman farming needs to be analyzed for Andaliman farming desires by lifting five dimensions of desire. The method used to analyze Andaliman is multidimensional scaling or MDS in a tool called Rapfish with the output of sensitive attribute data and the value of the desire index of each dimension. The results of the study showed that the value of the desire index for Andaliman farming and cultivation in the fairly sustainable category with a desire ordination value of 54.44 and 51.54. Sensitive attributes that affect the sustainability of andaliman farming are Planting materials for regeneration, Crop rotation, Sales system, Income/harvest, Selling price of andaliman, Tradition of using andaliman, Family participation in farming, Cooperation between andaliman farmers and UMKM managers, Role of agricultural extension workers, Access to agricultural roads, Post-harvest technology. Role of agricultural extension workers, Marketing information of andaliman and Management information of andaliman.